STRUGGLE TO FORGET THE UNSPEAKABLE TRAGEDY IN SUSANNE BIER'S THINGS WE LOST IN THE FIRE: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - SYAADAH, NAILA (2011)
Things We Lost in the Fire by Susanne Bier is an interesting and touchable movie. The major problem of this study is how struggle to forget the unspeakable tragedy reflected in the movie Susanne Bier's Things We Lost in the Fire based on Individual Psychological Approach. Susanne Biers tries to create a character such as Audrey Burke to encourage the reader to see how her life if it is seen from individual psychological approach. The researcher employs qualitative research method. In this method, the researcher uses two data resources namely primary and secondary data sources. The primary data source is the movie Susanne Bier's Things We Lost in the Fire itself. The secondary data source is the books about individual psychology and the other source related to the analysis. The method of data collection is descriptive technique. Both of data are combined to analysis the movie. All data are tightly bundled to support the idea. The results of this study show that first, it is structural elements of the movie which presents unity. It appears in the exposition, complication, climax, and resolution of the story. Second, it is the individual psychological analysis shows the striving of a wife and mother to forget the tragedy happened in her life and it is a successfully effort. She can still be alive with her children. She is stronger in lightening her days with people around her especially her children, Dory and Harper Burke.